Fungal Enolase, β-Tubulin, and Chitin Are Detected in Brain Tissue from Alzheimer’s Disease Patients - Pisa, Diana; Alonso, Ruth; Rábano, Alberto; Horst, Michael N.; Carrasco, Luis (Frontiers in Microbiology, 2016)
Recent findings provide evidence that fungal structures can be detected in brain tissue from Alzheimer’s disease patients using rabbit polyclonal antibodies raised against whole fungal cells. In the present work, we have developed and tested specific antibodies that recognize the fungal proteins, enolase and B-tubulin, and an antibody that recognizes the fungal polysaccharide chitin. Consistent with our previous studies, a number of rounded yeast-like and hyphal structures were detected using these antibodies in brain sections from AD patients. Some of these structures were intracellular and, strikingly, some were found to be located inside nuclei from neurons, whereas other fungal structures were detected extracellularly. Corporya amylacea from AD patients also contained enolase and B-tubulin as revealed by these selective antibodies, but were devoid of fungal chitin. Importantly, brain sections from control subjects were usually negative for staining with the three antibodies. However, a few fungal structures can be observed in some control individuals. Collectively, these findings indicate the presence of two fungal proteins, enolase and B-tubulin, and the polysaccharide chitin, in CNS tissue from AD patients. These findings are consistent with our hypothesis that AD is caused by disseminated fungal infection.